2019
DOI: 10.1371/journal.pone.0212173
|View full text |Cite
|
Sign up to set email alerts
|

Users’ preferences and perceptions of the comprehensibility and readability of medication labels

Abstract: Objective To evaluate the labeling preferences of medication users and characterize their perceptions of the comprehensibility and readability of medication labels. Methods We conducted a population-based cross-sectional study of medication users aged 18 years or older in 10 Brazilian capital cities. Perceptions of the comprehensibility and readability of medication labels in relation to sociodemographic characteristics were evaluated by Poisson regression models with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
(16 reference statements)
0
11
0
2
Order By: Relevance
“…More so, patient education enhancement remains challenging in our society. Different levels of education and comprehension can easily lead to misunderstanding by pregnant women when selecting medications [16][17][18]. Medication during pregnancy is related to the health of both the mother and fetus, and it is unrealistic for all drugs to be contraindicated during this period.…”
Section: Resultsmentioning
confidence: 99%
“…More so, patient education enhancement remains challenging in our society. Different levels of education and comprehension can easily lead to misunderstanding by pregnant women when selecting medications [16][17][18]. Medication during pregnancy is related to the health of both the mother and fetus, and it is unrealistic for all drugs to be contraindicated during this period.…”
Section: Resultsmentioning
confidence: 99%
“…31 Package design of OTC medications can improve consumer safety by simply increasing the font size, highlighting the active ingredient and incorporating graphic images. [31][32][33]…”
Section: Packaging's Influence On Perception and Behaviourmentioning
confidence: 99%
“…As such, research specific to OTC drug packaging primarily focuses on improving health literacy and controlling accessibility with child-protective or limited-mobility elements. 16,17,20,[31][32][33] Package design is impactful on consumer perception and behaviour as it is with CPGs, but the implications can be very different. For example, design elements of OTC medication packaging, 'such as symbol-oriented signals, signal words, or colors, can significantly enhance the efficacy of information delivery'.…”
Section: Pharmaceutical and Otc Packagingmentioning
confidence: 99%
“…Most studies have revealed that staff do not consider the degree of the occurrences. Other than that it has mentioned usage of audit tools for frequent monitoring of the laboratories where it can identify the mistakes at the earlier stages and necessary precautions can be taken [18]. Different accredited bodies use such audit tools and compared with the ISO Audit checklist allows laboratory managers to get to know whether all procedures are meeting the expected requirements and if there is any deviation it can be detected early and apply the preventive measurements.…”
Section: Quality Managementmentioning
confidence: 99%